Highly Stable External Short-Circuit-Assisted Oxygen Ionic Transport Membrane Reactor for Carbon Dioxide Reduction Coupled with Methane Partial Oxidation - Zhang, K; Liu, Lihong; Sunarso, J.; Yu, H.; Pareek, Vishnu; Liu, Shaomin (American Chemical Society, 2014)
A membrane reactor allows for simultaneous separation and reaction, and thus, can play a good role to produce value-added chemicals. In this work, we demonstrated such a membrane reactor based on fluorite oxide samarium-doped ceria (SDC) using an external short-circuit concept for oxygen permeation. The fluorite phase was employed to impart its high structural stability, while its limited electronic conductivity was overcome by the application of an external short circuit tofunction the SDC membrane for oxygen transport. On one side of the membrane, i.e., feed side, carbon dioxide decomposition into carbon monoxide and oxygen was carried out with the aid of a Pt or Ag catalyst. The resultant oxygen was concurrently depleted on the membrane surface and transported to the other side of the membrane, favorably shifting this equilibrium-limitedreaction to the product side. The transported oxygen on the permeate side with the aid of a GdNi/Al2O3 catalyst was then consumed by the reaction with methane to form syngas, i.e., carbon monoxide and hydrogen. As such, the required driving force for gas transport through the membrane can be sustained by coupling two different reactions in one membrane reactor, whosestability to withstand these different gases at high temperatures is attained in this paper. We also examined the effect of the membrane thickness, oxygen ionic transport rate, and CO2 and CH4 flow rates to the membrane reactor performance. More importantly, here, we proved the feasibility of a highly stable membrane reactor based on an external short circuit as evidenced byachieving the constant performance in CO selectivity, CH4 conversion, CO2 conversion, and O2 flux during 100 h of operation and unaltered membrane structure after this operation together with the coking resistance.